Fungal tissue per se is stronger as a UV-B screen than secondary fungal extrolites in Lobaria pulmonaria. (April 2017) - Gauslaa, Yngvar; Alam, Md. Azharul; Lucas, Pierre-Louis; Chowdhury, Dipa Paul; Solhaug, Knut Asbjørn
Abstract: To test the hypotheses that (1) protective mycobiont tissues and/or (2) medullary UV-B-absorbing carbon-based secondary compounds (CBSCs) protect lichen photobionts against UV-B radiation, we quantified cortical UV-transmittance and ran a three-way factorial lab experiment with (1) three UV radiation regimes, (2) photobiont layers with/without a screening cortex, and (3) with natural/reduced CBSC-concentration. We used melanin-deficient Lobaria pulmonaria from shaded forests. Maximum photochemical efficiency of photosystem II ( F v/ F m) in photobionts inside thalli with natural CBSC-concentrations was not affected by any UV-regime, consistent with close to 0% measured cortical transmittance of wavelengths <325 nm. Exposing photobiont layers to direct radiation strongly aggravated photoinhibition ( P  < 0.001), as did an increase in UV-exposure ( P  < 0.001). The effect of CBSC-removal was weaker (yet significant at P  = 0.001), mainly affecting exposed photobiont layers given short-wavelength UV radiation. Based on these findings, we conclude that the primary role of extrolites in L. pulmonaria is not to screen excess solar radiation.